Comparison between warm-up protocols in post-activation potentiation enhancement (PAPE) of sprint and vertical jump performance in a female futsal team - Chaves Lucas, G.; Mendes Sá, S. A.; Nobre Pinheiro, B.; Godinho, I.; Casanova, F.; Machado Reis, V.; Garrido, N.; Vilaça-Alves, J. (Research Quarterly for Exercise and Sport, 2025)
The aim of this study was to examine the influence of three warm-up protocols, with and without post-activation performance enhancement (PAPE), on sprint and vertical jump performance in female athletes. Twenty-five university futsal athletes were randomly assigned to three protocols: i) Traditional Warm-Up (TWU), involving cardiovascular, coordination exercises, and dynamic stretching; ii) Drop Jump Warm-Up (DJWU), consisting of drop jumps from heights of 30 and 40 cm; and iii) Maximum Isometric Warm-Up (MIWU), with high-intensity isometric contractions held for 10 seconds in a squat position at approximately 130-135 degrees of knee flexion. Tests included the countermovement vertical jump (CMVJ) and a 20-meter sprint (S20). The CMVJ showed a significant increase across all three groups (F(1,72) = 125.312; p < .0001; np2 = 0.635), while S20 displayed a significant time reduction only for MIWU (p = .002). Although no significant differences were found between groups, individual analysis revealed significant CMVJ differences for TWU, DJWU, and MIWU (p < .0001). We conclude that PAPE effectiveness varies according to protocol and individual athlete characteristics; however, maximum isometric exercises appear to have a more pronounced effect on PAPE production in sprint performance.